2010
DOI: 10.1111/j.1468-3148.2010.00572.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric in-Patients Away From Home: Accounts by People With Intellectual Disabilities in Specialist Hospitals Outside Their Home Localities

Abstract: Background This study reflects a growing concern with the placement of people with intellectual disabilities and complex mental health problems in out of area placements at a distance from their families and communities. Materials and methods We interviewed service users (n = 17) living in out of area in-patient psychiatric units using a semi-structured interview as part of a service user consultation process. The questions addressed safety and security, food, facilities, day time activities, education, opport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 22 publications
3
33
0
Order By: Relevance
“…For example, movement to out of area placements as a result of challenging behaviour may add to an individual's stress and also reduce opportunities for information sharing (e.g. of past traumas and current triggers) by disrupting support systems with families, friends and services [37].…”
Section: Trauma and Challenging Behaviourmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, movement to out of area placements as a result of challenging behaviour may add to an individual's stress and also reduce opportunities for information sharing (e.g. of past traumas and current triggers) by disrupting support systems with families, friends and services [37].…”
Section: Trauma and Challenging Behaviourmentioning
confidence: 99%
“…Where behaviour is framed as problematic or challenging, an individual may be viewed only as a perpetrator rather than having been a victim in the past, and so, management may be more punitive than therapeutic for example with seclusion, restraints [38,39], being moved to out of area placements [37] and medication. Anti-psychotics are used extensively with people with intellectual disabilities [40], often controversially to manage behaviour where no underlying diagnosis such as PTSD has been identified and with limited evidence base for their clinical or cost-effectiveness [41,42].…”
Section: Trauma and Challenging Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…These placements, however, tend to be costly and vary in quality or, in some cases, perpetrate abusive practices (Department of Health (DoH), 2012) and decrease likelihood of community integration (SCIE, 2004;Barron et al, 2011;Chinn et al, 2011). UK data demonstrate that challenging behaviours are a major predictor of costs (Knapp et al, 2005) with one study reporting that relocation of ten service users with challenging behaviour into community living not only improved quality of life but saved around £900,000 per year (Association of Supported Living, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…. Elderly or disabled family members were particularly affected (Bonell et al, 2011;Chinn et al, 2011). reported that family contact declined the further the distance from their relative's placement, but surprisingly, the relatives of residents in campus settings reported a higher total number of contacts with their family members, than those in community housing.…”
Section: Introductionmentioning
confidence: 99%